Liquidity, Leverage, Activity, and Profitability Ratios on Financial Distress: Evidence from LQ45 Manufacturing Companies - Farhan Dzulfiqri; Yoyo Sudaryo; Nunung Ayu Sofiati; Andre Suryaningprang; Riyandi Nur Sumawidjaja (Green Publisher Indonesia, 2026)
This research examines the effect of liquidity, leverage, activity, and profitability on financial distress among manufacturing companies included in the LQ45 Index in Indonesia during 2020–2024. This research used a quantitative explanatory approach to investigate the relationship between the variables. The analysis relied on secondary data obtained from the audited annual reports of 7 manufacturing companies selected by purposive sampling method, resulting in a balanced panel dataset consisting of 35 observations. Financial distress was measured using the Altman Z-Score, while TATO, ROA, DER, and CR were employed as the independent variables. To evaluate both the individual and combined effects of these variables on financial distress, panel data regression analysis was conducted using the CEM, supported by t-test and F-test analysis. The results reveal that liquidity (t = 2.426; p = 0.022) and profitability (p = 0.070) have positive and statistically significant correlations with the Altman Z-Score, indicating that stronger liquidity and higher profitability mitigate financial distress risk, with profitability emerging as the dominant predictor. Conversely, leverage and asset efficiency show no significant individual effects, suggesting that manufacturing firms can adjust their capital structure and asset utilization without necessarily increasing financial distress risk. However, when all four ratios are considered simultaneously, they collectively explain a substantial portion of the variation in financial distress (F = 3.797; p = 0.013; R² = 33.61%). These findings highlight that financial ratio indicators, particularly those related to liquidity and profitability, are useful for evaluating the financial health of established manufacturing firms in Indonesia's LQ45 Index.